Optimization of photosynthesis for sustainable crop production - Seid Hussen Muhie (CABI Agriculture and Bioscience)
Abstract Crop production will need to increase by about 60% to satisfy the demand of food for the fast-growing population globally. A number of recent studies have provided strong support demonstrating that improving the photosynthetic efficiency via different systems can provide an avenue to improve yield potential of crops. Photosynthesis a regulated system that drives biological processes including crop yields. Hence, this review focuses on improvement of the efficiency of photosynthesis via different mechanisms; decreasing photorespiration, transforming C3 crops to C4 pathway, optimization of Calvin Benson cycle / Rubisco, and electron transport. Further work should be done on transgenic crops with modified photosynthesis. Optimization of the activity of Rubisco may not be successful in some moisture stress areas, and consideration of photoprotection could offer some advantages. Optimization of source-sink relationship would represent another promising way to improve crop yield. A strong sink can increase crop yield even under stress conditions.